EFEKTIFITAS KOMPRES PANAS DAN DINGIN TERHADAP PENURUNAN NYERI PERSALINAN KALA I FASE AKTIF - Suci Hakameri, Cecen; Irianti, Berliana; Israyati, Nur; Nurhapipa, Nurhapipa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Labor pain can affect uterine contractions through the secretion of catecholamine and cortisol levels, which increase sympathetic nervous system activity, causing changes in blood pressure, heart rate, and respiration, and ultimately affecting the duration of labor. This study aimed to evaluate the effectiveness of hot and cold compresses in reducing labor pain during the active phase of the first stage of labor at PMB Ernita Pekanbaru. The research employed a pretest-posttest method in a group of laboring mothers, measuring pain scales before and after the intervention.The results showed that the majority of labor pain levels without hot compresses (pretest) were in the category of very severe pain with a pain scale of 7–8 (73.3%). After applying hot compresses (posttest), the majority of pain levels decreased to severe pain with a pain scale of 5–6 (73.3%). Meanwhile, the majority of labor pain levels without cold compresses (pretest) were categorized as very severe pain (46.7%) and unbearable pain (46.7%) with a pain scale of 7–10. After applying cold compresses (posttest), the majority of pain levels decreased to severe pain with a pain scale of 5–6 (53.3%).Data analysis showed a significant effect of hot and cold compresses on reducing labor pain during the active phase of the first stage of labor, with a p-value of 0.000. Therefore, hot and cold compresses can be recommended as effective non-pharmacological interventions to reduce labor pain and support a more comfortable and efficient labor process.Keywords: Hot compress, cold compress, labor pain, active phase of the first stage of labor